Co-transplantation of Mesenchymal Stromal Cells and Induced Pluripotent Stem Cell-Derived Cardiomyocytes Improves Cardiac Function After Myocardial Damage - Neef, Klaus; Drey, Florian; Lepperhof, Vera; Wahlers, Thorsten; Hescheler, Jürgen; Choi, Yeong-Hoon; Šarić, Tomo (Frontiers in Cardiovascular Medicine, 2022)
Induced pluripotent stem cell-derived cardiomyocytes (iPS-CM) represent an attractive resource for cardiac regeneration. However, survival and functional integration of transplanted iPS-CM is poor and remains a major challenge for the development of effective therapies. We hypothesized that paracrine effects of co-transplanted mesenchymal stromal cells (MSC) augment the retention and therapeutic efficacy of iPS-CM in a mouse model of myocardial infarction (MI). To test this, either iPS-CM, MSC or both cell types were transplanted into the cryoinfarction border zone of syngeneic mice immediately after injury. Bioluminescence imaging of iPS-CM did not confirm enhanced retention by co-application of MSC during the 28-day follow-up period. However, histological analyses of hearts 28 days after cell transplantation showed that MSC increased the fraction of animals with detectable iPS-CM by two-fold. Cardiac MRI analyses showed that from day 14 after transplantation on, that animals having received cells had a significantly higher left ventricular ejection fraction (LVEF) compared to the placebo group. There was no statistically significant difference in LVEF between animals transplanted only with iPS-CM or only with MSC. However, combined iPS-CM and MSC transplantation resulted in higher LVEF compared to transplantation of single cell populations during the whole observation period. Histological analyses revealed that MSC increased the capillarization in myocardium when transplanted alone or with iPS-CM and decreased the infarct scar area only when transplanted in combination with iPS-CM. These results indicate that co-transplantation of iPS-CM and MSC improves cardiac regeneration after cardiac damage, demonstrating the potential of combining multiple cell types for increasing the efficacy of future cardiac cell therapies.